Can ASEAN Cope with China?. Issue 1 (April 2016) - Beeson, Mark
The rise of China is the most important development in East Asia in recent times. It presents major opportunities and challenges, if not threats, for ASEAN as a collective entity, and for the individual countries that compose it. Whether ASEAN can develop a collective, let alone effective response is far from clear. This paper explores and analyses the forces that are likely to determine the outcome.